Effect of Positional Changes on Skin Landmarks in Midface Filling. (6th June 2022) - Du, Yuyang; Ye, Yajie; Wang, Qing; Li, Meijia; Chen, Xinyao; Li, Rou; Hao, Lijun; Luo, Sai
Abstract: Background: The design lines for midfacial filling shift upward with a patient's position changes from upright to supine during operation. This will cause the actual filled part to deviate from the target area. Objectives: This authors aimed to evaluate the effect of positional changes on midfacial landmarks and find the optimal body position for midface filling. Methods: The process involved the grading and evaluation stages. The midfacial laxity of each sample in the evaluation stage was graded into minimal, moderate, and severe by the system established in the grading stage. Measured through the 3-dimensional images in each grade, the vertical distances from landmarks C, D, and E (representing the region of the tear trough, infraorbital area, and nasolabial fat pad, respectively) to the horizontal line of the inner canthus and depth of nasolabial fold at an angle of 90° were separately compared with those from the other angles (60°, 45°, 30°, and 0°) of the operating table. Results: In the minimal midfacial laxity group, all 3 landmarks significantly moved upward when the angle decreased to 30°. However, landmark E of the moderate and severe and landmark D of the severe midfacial laxity groups both significantly moved upward when the angle decreased to 45°. The depth of the nasolabial fold at a 45° angle was significantly less than that at a 90° angle in the moderate and severe groups. Conclusions: In midface filling, a patient's body position should be optimally selected according to the midfacial laxity and filling area.